Evaluation of Coupling and Coordinated Development of Marine Economic Policy and Marine Service Industry - Lv Zuoliang; Li Bin (E3S Web of Conferences, 2021)
This article studies the coordinated development of marine economic policy and marine service industry by constructing a system for evaluating marine economic policy and marine service industry indicators and applying a coupled coordination degree model, and analyzes its development laws. The research shows that the coordinated development level of marine economic policy and marine service industry is on the rise, the interaction level among the elements in the system is enhanced, the cyclic cumulative causal effect and cluster advantage are enhanced, and the coordinated development level is adjusted from primary imbalance to primary coordination. Under the comprehensive effect of the stable curve law of the development of marine economic policies and the stable rising law of the development of marine service industry, the development of marine service industry is in good condition, and the development of marine economic policies lags behind. To further promote the high-quality development of marine service industry, the government can strengthen Guide the connection between the main factors of the two systems and the positive and dynamic response to further promote the coordinated development of the two.